Cervical spine magnetic resonance imaging in primary care consulters with shoulder pain: a case–control study. Issue 10 (8th February 2007) - Paul, Anindita; Lewis, Martyn; Saklatvala, Jackie; McCall, Iain; Shadforth, Mike; Croft, Peter; Hay, Elaine
Abstract : Objectives: To investigate the association between shoulder region pain presenting in primary care and cervical spine magnetic resonance imaging (MRI) abnormalities. Methods: A matched case–control study of 48 pairs of participants. Patients had presented to primary care with a new episode of shoulder pain. Controls had no history of pain in the shoulder region and were individually matched with cases by age, gender and referring clinician. All participants underwent a structured clinical assessment and cervical spine MRI. Scans were scored by experienced musculoskeletal radiologists blinded to case–control status. Results: Median age of participants was 51 years (range 19–79) and 21 (44%) were female. "Neck pain in the past week" was reported by 25 (52%) cases and seven (15%) controls (odds ratio, OR, 10.0; 95% confidence interval, CI, 2.4, 88.2). Cervical spine MRI from C3/4 to C6/7 revealed: 18 (38%) of both cases and controls had disc height loss ⩾50% at any level; 10 (21%) cases and eight (17%) controls had disc disease with neural compromise; 11 (23%) cases and 16 (33%) controls had foraminal stenosis; nine (19%) of both cases and controls had canal narrowing. At least one of the above findings was present in 24 (50%) cases and 23 (48%) controls (OR 1.1; 95% CI 0.4, 3.4). Conclusions: Cervical spine MRI abnormalities were similar in both cases and controls, despite significantly more self-reported neck pain in cases with shoulder pain. Other possible mechanisms, such as muscular strain or postural problems, may explain the observed clinical association between shoulder region pain and neck associated symptoms.